Light Effect on Germination of Champa (Campomanesia lineatifolia R. & P.) seeds - Porras Merchan, Yenny Catherin; Pedreros Benavides, Maria Camila; Reyes Ardila, Wendy Lorena; Balaguera Lopez, Helber Enrique (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Champa (Campomanesia lineatifolia R. & P.), is a fruit species of the Mirtaceae family with high trading potential due to the palatability of its fruits. Its spread by seeds has difficulties related to a low germination percentage and a long time to complete this stage. Taking into account that the effect of the light on champa seeds is unknown, the objective of this study was to determine the effect of different light treatments on the germination of champa seeds under laboratory conditions. The plant material was collected in Miraflores, a municipality of Boyacá state in Colombia. An experiment was carried out in a completely randomized design with 4 treatments corresponding to different light conditions, for which the seeds were sown in Petri dishes that were covered with aluminum foil (dark), red cellophane paper, blue cellophane paper and one group was not covered (control). Each treatment had 4 repetitions, the experimental unit was composed of a Petri dish with 35 seeds. Germination and viability (tetrazolium test) parameters were determined. The maximum germination percentage (57.85%) and the highest germination speed (0.39 germinated seeds/d) were obtained with the red light treatment, the opposite response was obtained with the seeds in the dark. The freshly harvested seeds presented 93.74% viability. The seeds that did not germinate had a representative percentage of viable seeds (between 15 and 20%). These results allow us to conclude that C. lineatifolia has a positive photoblastism behavior and presents dormancy conditions, possibly physiological dormancy.